Dissemination of Children's Literary Work to Optimize Virtual Language Laboratory at Elementary School Education Department - Asri Susetyo Rukmi; Sukartiningsih, Wahyu; Subrata, Heru; Damayanti, Maryam Isnaini; Hendratno; Istiq'faroh, Nurul (Journal of Educational Technology and Instruction, 2023)
The rapid development of Science and Technology (IPTEK) in the 21st century has led to changes in curriculum, media, and technology. Good learning media can make abstract concepts to be easily understood. The 21st century learning requires ICT-based learning which requires interactive media. Teachers must ensure that learning can run well and learning objectives can be achieved. Virtual laboratories can be used in learning (VLab). VLab can be utilized in class or for self-learning. Virtual lab-based learning overcomes 21st-century learning difficulties. The virtual laboratory is an interactive medium where students can observe phenomena in order to fulfill learning objectives. The results of the study show that (1) The Language VLab at http://pgsd.fip.unesa.ac.id/page/vilab-language is feasible to use. The user response test to VLab Language shows 84.5% feasibility. The results of VLab Language dissemination have been optimal that can be seen through the enthusiasm of VLab Language visitors; (2)The results of data collection showed that 50% of students, 30% of lecturers, and 20% of professors visited the Language VLab. Students frequently visit the Language VLab. While, the title of the fairy tale book that is often read and downloaded by readers is entitled "The Country of Learning".